Short-term oxidation behavior of Cr-coated Zr-1Nb in severe accident environments: steam and air - Donghui Geng; Jianxi Deng; Shangle Huo; Qiaoyan Sun; Zhongxiao Song; Sigong Li; Jiaxiang Xue; Yehong Liao; Jun Sun (npj Materials Degradation)
Abstract This study examines Cr-coated Zr-1Nb alloy cladding oxidation in steam/air (600–1200 °C), simulating accident scenarios. Thermogravimetry and static air tests revealed Cr coatings form granular oxides in air and coral/worm-like structures in steam (H2 release-driven). Cr3+ migration governs oxidation kinetics. At 1000 °C air (>40 min), weight gain deviates from parabolic kinetics due to ZrN/ZrO2 phase transitions, causing porous oxide formation. Air yields thinner Cr2O3 layers than steam at 800–1000 °C, as Cr2O3 reacts with O2 to form volatile CrO3. At 1200 °C air (>40 min), Cr2O3 thinning occurs due to dominant volatilization over diffusion. Results confirm Cr coatings delay Zr substrate oxidation during LOCAs by suppressing rapid degradation under extreme heat, enhancing accident tolerance. The balance between Cr2O3 thickening induced by diffusion and thinning induced by volatilization defines protective efficacy, validating the role of Cr in accident-tolerant fuel cladding.